Official "funas": Free speech and tolerance in the Universities: The case of San Alberto Hurtado Association in the Catholic University - Pablo Pérez, Rodrigo (Derecho Público Iberoamericano, 2021)
This article analyzes a case that occurred at the Catholic University of Chile in which two students were persecuted for hanging a sign that read “children have the right to have a father xy and a mother xx”. It was an untidy process full of abuses, in which it can be seen how the university authorities cede in their role of protecting the purposes of the university and educating students in a way that promotes tolerance and democracy.